Retention and Distribution by Healthy Young Men of Stable Isotopes of Selenium Consumed as Selenite, Selenate or Hydroponically-Grown Broccoli Are Dependent on the Isotopic Form - Finley, John W (The Journal of nutrition, 1999)
Twenty-seven healthy young men were randomly assigned to diets that supplied low (32.6 micrograms/d) or high (226.5 micrograms/d) levels of selenium for a 105-d study. After consuming the diets for 85 d, subjects were fed a test meal that contained 74Se in the form of selenite or selenate and 82Se incorporated into hydroponically-raised broccoli. Urine, fecal and blood samples were collected daily. Isotope absorption was not different (P > 0.05) for selenate and Se in broccoli; Se absorption from selenite was highly variable and was not included in statistical analyses. Significantly more isotope was absorbed by subjects fed the high Se diet (P = 0.015). Urinary isotope excretion was greater when selenate was fed than when broccoli was fed (P = 0.0001), and consequently more Se from broccoli (as compared to selenate) was retained (59.2 ± 2.4 and 36.4 ± 4.6% for Se in broccoli and selenate, respectively; P = 0.0001). Despite the higher retention, less isotope from broccoli than from selenate was present in the plasma. Plasma proteins separated by gel permeation chromatography showed that most of the isotopes were distributed between two medium molecular weight peaks. Less isotope was found in plasma proteins of subjects fed the high Se diet, but the form of Se had no effect on isotope distribution. These results show that dietary Se intake alters the retention of stable isotopes of Se and that humans retain and distribute Se from broccoli in a different manner than Se from inorganic salts.